ESTUDIO DE EMPLEABILIDAD DE LA MAESTRÍA DE DERECHO CONSTITUCIONAL. - Román Rodríguez, Jennifer (2015)
The purpose of this article is to study the employability of the MSc in Constitutional Rights' graduates from the Ecuadorian university Espíritu Santo. Through an empirical study, a questionnaire was applied to all graduates of the cohorts starting in 2010, 2011, 2012 and 2013; this questionnaire was designed taking into consideration some factors from the basic graduates scheme, following the Ley de Educación Superior, the Reglamento de Régimen Académico and the accreditation norms for careers and programmes. The general data of graduates, their situation and work history; and their perceptions about the program they followed and their institution were obtained.